Prisoner reentry and the life course - LeBel, Thomas P. (The Oxford handbook of developmental psychology and the law, 2024)
This chapter addresses prisoner reentry and the life course. It focuses on three distinct phases or timeframes: what happened in the life course for many individuals before arriving at the prison gate, events that take place while incarcerated, and what transpires after release from prison. Although recidivism (rearrest, conviction, return to prison) is discussed, the chapter also examines other important life course events or outcomes such as employment, housing, family relationships/marriage, and health. Other factors that make achieving a successful life (maximizing one’s potential) difficult for formerly incarcerated persons are described such as the stigma of incarceration and the collateral (legal) consequences of a felony conviction. The chapter concludes by discussing directions for future research.